Professionalising career guidance : practitioner competences and qualification routes in Europe - (:unkn) unknown (Office for Official Publications of the European Communities, 2009)
"The competence of career guidance staff makes an essential contribution to the quality of career guidance services. This report confirms that current training provision for such staff is highly variable between countries and sectors in Europe, although there is clear movement towards more specialised training. Opportunities for staff mobility are limited, particularly between education and labour market sectors and from paraprofessional to professional roles. The review reports recent trends in training provision, key issues requiring attention and possible actions by policy makers, trainers and practitioners. It includes six detailed case studies of countries that have taken coordinated action to address national issues. The report addresses the concept of competence and defines the specific competences needed by career guidance practitioners. It proposes a competence framework relevant to their work, and explores the ways in which the competence framework may be used, including the creation of more flexible and coherent training pathways for individual staff." (Hrsg., BIBB-Doku)
Keywords: L 5 Beratung & Orientierung; G 1.2.3.2 Anforderungen & Bedarfe; P 3.1 Beratungsdienstleister; I 1.2 Anrechnung im Ausland erworbener Leistungen & Abschlüsse; I 2.2 Europa; Berufsberatung; Bildungsberatung; Qualifikationsanforderung; Professionalisierung; Europäischer Qualifikationsrahmen; Fallbeispiel; Bulgarien; Dänemark; Irland; Lettland; Polen; Schottland; Europa